Predictors of Mortality and Limb Loss in Necrotizing Soft Tissue Infections. Issue 10 (October 2013) - Schwartz, Samuel; Kightlinger, Elizabeth; Virgilio, Christian De; Virgilio, Michael De; Kaji, Amy; Neville, Angela; Bennion, Robert; Saltzman, Darin J.
Necrotizing soft tissue infections (NSTIs) require prompt diagnosis and treatment. Early identification of patients at greatest risk of limb amputation and death may help in targeting aggressive medical and surgical management. The aim of this study was to assess predictors of limb loss and mortality in patients with NSTI based on admission variables. We performed a retrospective review of two hospitals that care for a large volume of patients with NSTI. Univariate and multi-variable analyses were used to determine the association of admission biochemical markers to limb loss and mortality. Of 174 patients with NSTI, there were 19 deaths (10.9%) and 42 required amputations (24.1%). Multivariable logistic regression analysis revealed that only arterial lactate was predictive for both mortality (odds ratio [OR], 1.5; 95% confidence interval [CI], 1.1 to 2.0; P = 0.009) and limb loss (OR, 1.3; 95% CI, 1.0 to 1.7; P = 0.02). In patients with a suspected NSTI, an arterial lactate should be ordered early on to guide aggressive therapeutic interventions and to provide information with regard to long-term outcomes of amputation and death that is needed for early discussion with the patient and family.